(3JaSjQ GdLdGdjfs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3gs
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg ehGajG dfYeg gPG eG GTJOJ Edjg MGLI GdQGZHjf aj JcedI JaSjQ GdbQBf GdPj Cdag LdGd GdOjf GdeMdj s
(3BNQgG (B:s
(3ZjQ GdeZVhH Ydjge hge GdjghO hdG GdVGdjf hge GdfUGQi hfcJI GdHOd EaGOI Cf GdegOjjf djShG jghOG hdG fUGQi hGddg JYGdi CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 /301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 445s
(3TPQGJ GdPgH (B7 / 303 (3, (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs